Effectiveness of Online Learning Tools for Improving Speaking Skills in English Education - Jumadil Akbar, Jumadil Akbar (Lembaga Bale Literasi, 2024)
Especially speaking in language is very important, but the factor of speaking anxiety, vocabulary limitation and little real conversation exposure are a few struggles speaking learners usually face. Abstract purpose this paper aims to conduct a systematic literature review of 20 peer-reviewed journal articles published between 2017 and 2023 on the effectiveness of online learning tools in improving English speaking skills. The effect of tools such as YouTube videos, simulation-based platforms and speech recognition software on fluency (automaticity), pronunciation, and vocabulary were considered. The data shows that YouTube can enhance vocabulary and pronunciation, simulation-based tools improve fluency by providing realistic conversational context. Tools for Speech recognition encourage self-correction in learners and therefore add engagement to learners. Challenges however include poor technical accessibility, poor teacher training therefore constrained curricular integration for the tools to be used to their optimum level. Breaking through these barriers involves investments in digital infrastructure, teacher professional development, and equity. Research in this direction should consider long-term effects, curriculum integration and the potential such state-of-the-art technologies as artificial intelligence in personalized learning.